Structured warrant pricing in Singapore. - Koh, Jessica Mun Yee. (2008)
Prior studies have mentioned that warrants were found to be overpriced in the respective markets included in those studies but it seems that no previous research has been done on Singapore’s warrants market. The main objective of this paper is to explore whether the issue of overpricing applies to Singapore as well. We will also look into other areas such as whether all issuers overprice structured warrants and which particular issuer overprices to a greater extent. To find out, we carry out paired-samples t-tests and one-way analysis of variance test. Our sample includes only European structured warrants that are issued on a single stock. Our study reveals that structured warrants in the Singapore market are generally overpriced. Further tests reveal that all twelve issuers overprice their structured warrants. Among the four largest issuers, we observe that BNP Paribas (BNP) and Macquarie Bank (MBL) overprice structured warrants more than Deutsche Bank (DB) and Soci?t? G?n?rale (SG).